2012
DOI: 10.1002/j.2168-9830.2012.tb00053.x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Investigation of the Ethical Behavior of Engineering Undergraduates

Abstract: BACKGROUNDRecent national reports have indicated the need for an increased emphasis on the ethical development of engineering undergraduates. Despite this call for increased focus on ethical development, little is known about how engineering students make ethical decisions or how these decisions are related to personal differences and environmental influences. PURPOSE (HYPOTHESIS)This is an exploratory investigation to determine which demographic, academic, moral reasoning, and decision-making variables are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…The results from PACES-2 found that freshman (first-year) engineering students cheated more than senior students [12]. However, this is counter to results from PACES-1 where first-year students reported cheating on exams less than upper-year students [22].…”
Section: Demographic Factors That Influence Academic Dishonestymentioning
confidence: 78%
See 2 more Smart Citations
“…The results from PACES-2 found that freshman (first-year) engineering students cheated more than senior students [12]. However, this is counter to results from PACES-1 where first-year students reported cheating on exams less than upper-year students [22].…”
Section: Demographic Factors That Influence Academic Dishonestymentioning
confidence: 78%
“…After instructing these students on what constituted academic dishonesty, they did not perform differently than domestic students [25]. Although international students may be initially unclear on what constitutes cheating, PACES-2 found no correlation between an engineering student's international status and their inclination to cheat [12]. It seems that initial instruction on what is expected of international students could eliminate any additional predilection toward academic dishonesty.…”
Section: Demographic Factors That Influence Academic Dishonestymentioning
confidence: 91%
See 1 more Smart Citation
“…A large portion of the literature in engineering education related to ethics has focused on content and pedagogy and general ethical (or unethical) behaviors such as cheating or participation in pro-social activities 2,3,4,5,6 . However, an increasing number of studies are investigating foundational considerations such as student levels of moral development or student perceptions of, and attitudes toward, social and ethical responsibility.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…To measure this, we included questions drawn from the SEED survey 22,24,26,35 . From this instrument, we extracted three measures of satisfaction with ethics education: (a) a 6-item scale (α = .85) measuring satisfaction with particular kinds of educational activities, such as class discussions, credit courses, extracurricular workshops; (b) a 6-item scale (α = .91) measuring satisfaction with particular concepts covered during ethics education, such as being taught about ethical codes, recognizing ethical issues, learning decision-making, and the ability to justify ethical decisions with theory; and (c) a single item measuring general satisfaction with the quality of ethics education received 25 .…”
Section: Methodsmentioning
confidence: 99%